Kết quả nghiên cứu chọn tạo giống đậu tương DT-95 - Mai, Quang Vinh (2011)
Tác giả: Mai Quang Vinh, PGS.TS; Mai Quang Vinh, PGS.TS; Trần Văn Lài, GS.PTS; Ngô Phương Thịnh, CN; Trần Thuý Oanh, KS -- Từ khóa: Đậu tương